2019
DOI: 10.3846/jbem.2019.11321
|View full text |Cite
|
Sign up to set email alerts
|

The Economy-Energy-Environment Nexus in Imf’s Top 2 Biggest Economies: A Ty Approach

Abstract: This paper assesses the relationship between carbon emissions, economic growth and, energy consumption, in USA and China from the perspective of Granger causality, in a multivariate framework controlling for financial development, urbanization, and trade openness. Econometric techniques employed include unit root tests, Toda and Yamamoto Granger causality, and generalized impulse response and variance decomposition analysis for the time horizon 1980–2017. Test results indicate that governments of the USA and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Then in 2019, there were two studies using units of analysis from various countries, including research by [26,27]. Then, in 2020, there was only one study using a multi-country unit of analysis, conducted by [28]. In 2021, research using objects from various countries began to be widely used, including research by [29][30][31][32][33][34][35].…”
Section: Mapping Based On Unit Analysismentioning
confidence: 99%
“…Then in 2019, there were two studies using units of analysis from various countries, including research by [26,27]. Then, in 2020, there was only one study using a multi-country unit of analysis, conducted by [28]. In 2021, research using objects from various countries began to be widely used, including research by [29][30][31][32][33][34][35].…”
Section: Mapping Based On Unit Analysismentioning
confidence: 99%
“…Strong transmission effects are confirmed between social behavior and environmental security (Ahmed et al, 2019;Holotová et al, 2020;Vafaei et al, 2019) as well as entrepreneurial sustainable policy, which creates new prospects to enhance environmental and national security (Alimuddin et al, 2020;Atkociuniene & Mikalauskiene, 2019;Nikodemska-Wołowik et al, 2019;Romana, 2020;Vasylieva et al, 2017). Studies of the relationship between different types of national security have shown that the closest interaction exists in the group "environmental-energy-economic security" (Atta Mills et al, 2020). Thus, energy and environmental security are connected through the structure of energy production (Jonek-Kowalska, 2019;Kolosok et al, 2020), development of alternative energies (Cebula et al, 2018;Prokopenko et al, 2017), sustainable and green investment (Pavlyk, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, scientists also argued that environmental policy's main vectors are closely dependent on the country's energy security and priorities. Specifically, Atta Mills, Zeng, and Baafi (2020), based on the analysis of data on carbon emissions, economic growth and energy consumption in the USA and China in 1980-2017 using the Granger causality test, found out that in these two countries there is an inverse dependency between the scale of energy use and country economic development, while there is no statistically significant evidence of greenhouse gas emission on the economic welfare of both countries. Thus, we can underline that the priority vector of environmental policy for some developed economies is not highly connected to the air pollution, but to the environmental modernization of energy sector, responsible energy consumption, and expansion of renewable electricity production.…”
Section: Literature Reviewmentioning
confidence: 99%